Impact Study of DAAI TV Humanistic Broadcasting: Stories of Two Families - Mandasari, Rahma Widayanti (Politeknik Negeri Padang, 2017)
This study was inspired by the finding of the previous research that is related to positive impact in viewers’ life after watching anti mainstream television shows. The television show is broadcasted by television channel which committed to show humanistic program which has the value of grateful, dutiful to parents as obligation, empathy for others without discrimination and caring character to environment. This research subject are loyal viewers of private television in Indonesia. The research method used is a case study where the researcher become the main instrument in conducting this research. The other instruments are field notes, observation result, documentation, and in-depth interviews. Research result shows that television channel namely DAAI TV give positive impact to viewers, such as being a grateful person, dutiful to parents, being a person who benefits other by volunteering for the community and has the character who love environment..